Age disparities in lung cancer survival in New Zealand: The role of patient and clinical factors. (July 2021) - Pilleron, Sophie; Maringe, Camille; Charvat, Hadrien; Atkinson, June; Morris, Eva; Sarfati, Diana
Highlights: We studied the influence of patient and clinical factors on age pattern in lung cancer survival. Age disparity in lung cancer survival were strongest in women and non-advanced cancer. Deprivation, ethnicity, comorbidity, and emergency presentation had no influence. There is a need a better representation of older adults in clinical trials. Geriatric assessment will identify patients who will benefit treatment. Abstract: Objective: Age is an important prognostic factor for lung cancer. However, no studies have investigated the age difference in lung cancer survival per se. We, therefore, described the role of patient-related and clinical factors on the age pattern in lung cancer excess mortality hazard by stage at diagnosis in New Zealand. Materials and Methods: We extracted 22 487 new lung cancer cases aged 50–99 (median age = 71, 47.1 % females) diagnosed between 1 January 2006 and 31 July 2017 from the New Zealand population-based cancer registry and followed up to December 2019. We modelled the effect of age at diagnosis, sex, ethnicity, deprivation, comorbidity, and emergency presentation on the excess mortality hazard by stage at diagnosis, and we derived corresponding lung cancer net survival. Results: The age difference in net survival was particularly marked for localised and regional lung cancers, with a sharp decline in survival from the age of 70. No identified factors influenced age disparities in patients with localised cancer. However, for other stages, females had a greater difference in survival between middle-age and older-age than males. Comorbidity and emergency presentation played a minor role. Ethnicity and deprivation did not influence age disparities in lung cancer survival. Conclusion: Sex and stage at diagnosis were the most important factors of age disparities in lung cancer survival in New Zealand.